Cybersecurity program for Philippine higher education institutions: A multiple-case study - Noly M. De Ramos; Francisco Dente Esponilla II (International Journal of Evaluation and Research in Education (IJERE), 2022)
Digital technology has become an integral aspect of an educational system. Every state university funded the creation of Information Technology Offices to secure its Management Information System. The challenge on cybersecurity threatens the intellectual capital of students especially in a research university, theft of crucial information, and financial loss. The current study is a multiple case study of cybersecurity threats and challenges of Selected Philippine State Universities and Colleges in the National Capital Region. Sample participants were purposively selected Information Technology experts from various selected State College and Universities. A structured interview as the main instrument of the study investigated threats and challenges of cybersecurity to assess active and proactive approaches to developing a model framework for security resources in respective academic institutions. Responses gathered from the interview were consolidated and analyzed through a thematic coding process. The result of the study revealed the following challenges in cybersecurity are user education, cloud security, information security strategy, and unsecured personal devices. The creation of a program logic model will provide an informed cybersecurity planning, implementation, and assessment framework to the commission on higher education in collaboration with the Department of Information and Communication Technology, and the Philippine Association of the State Colleges and Universities.